Fast and Slow Responses of the Indian Summer Monsoon to the Direct Radiative Effect of West Asian Dust Aerosols - Wang, Anqi; Xie, Xiaoning; Liu, Xiaodong; Shi, Zhengguo (Frontiers in Environmental Science, 2022)
The direct radiative effect (DRE) of west Asian dust aerosols can modulate the Indian summer monsoon (ISM) through by directly heating the atmosphere (fast response) and cooling the sea surface (slow response). However, the relative contributions between fast and slow responses are unclear. In this study, the Community Atmospheric Model 4 (CAM4) with an updated Bulk Aerosol Mode (BAM) has been used to identify these different responses of the ISM to the dust DRE. Our results show that the DRE of the west Asian deserts (WAD) dust significantly enhances ISM during the early monsoon season but weakens it during the late monsoon. Further analysis shows that the fast response heats the lower troposphere over WAD and the adjacent ocean, strengthens the southwesterly flows over the Arabian Sea, and thus increases the precipitation in central and eastern India (CEI), which dominates the ISM enhancement during the early monsoon season (May-June). During the late monsoon season (July-August), the slow response cools the sea surface temperature (SST) and the lower troposphere over Arabian Sea, creates the easterly flows to inhibit the moisture transport and decreases the CEI precipitation, ultimately weakening the ISM. Additionally, observational evidence of the trends in west Asian dust and CEI precipitation from 1980 to 2015 supports our simulated results. Our results suggest that the dust DRE induced ocean feedback plays a non-negligible role in modulating cross-seasonal climate effect of dust aerosols.